Дослідження сутності професійної правосвідомості юриста - Куренда, Л.; Kurenda, L. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2014)
У науковій статті автором проводиться аналіз наукових поглядів про сутність професійної правосвідомості юриста через призму її розмежування від правосвідомості. Автором розкривається основні ознаки професійної правосвідомості юриста, якими виступають професійне зайняття юридичною діяльністю, наявність спеціальної освітньої і практичної підготовки її суб’єктів, які утворюють професійну групу. Подається авторське розуміння терміну «професійна правосвідомість», що може вживатися для позначення поняття, яке відбиває правову свідомість юристів як соціальної групи і якісно своєрідний рівень сприйняття правових явищ. In this scientific article the author analyzes scientific views about the essence of professional legal awareness of lawyer through the prism of its delineation from legal awareness. The author reveals the basic features of the lawyer’s professional legal awareness that are shown by his professional legal activities, availability of special education and practical training of its subjects, which form a professional group. A new understanding of the term "professional legal awareness" was formulated by the author. It can be used to refer to a concept that reflects the legal consciousness of lawyers as a social group and qualitatively distinctive level of perception of legal phenomena. In other words, the professional legal awareness can be investigated either as a kind of collective or as a specific way of mastering the legal reality. Moreover, we believe that its interpretation solely as legal consciousness of lawyers is one-sided and incomplete. It focuses on the study of the problems of forming a collective professional legal awareness, its interaction and relationship with individual and public legal awareness.
Study of the Essence of Professional Legal Awareness of Lawyer
Keywords: професія; свідомість; правосвідомість; юрист; діяльність; правозахист; profession; consciousness; legal awareness; lawyer; activities; defense of rights